Aberrant splicing in neuroblastoma generates RNA-fusion transcripts and provides vulnerability to spliceosome inhibitors. Issue 5 (8th February 2021) - Shi, Yao; Yuan, Juan; Rraklli, Vilma; Maxymovitz, Eva; Cipullo, Miriam; Liu, Mingzhi; Li, Shuijie; Westerlund, Isabelle; Bedoya-Reina, Oscar C; Bullova, Petra; Rorbach, Joanna; Juhlin, C Christofer; et al.
Abstract: The paucity of recurrent mutations has hampered efforts to understand and treat neuroblastoma. Alternative splicing and splicing-dependent RNA-fusions represent mechanisms able to increase the gene product repertoire but their role in neuroblastoma remains largely unexplored. Here we investigate the presence and possible roles of aberrant splicing and splicing-dependent RNA-fusion transcripts in neuroblastoma. In addition, we attend to establish whether the spliceosome can be targeted to treat neuroblastoma. Through analysis of RNA-sequenced neuroblastoma we show that elevated expression of splicing factors is a strong predictor of poor clinical outcome. Furthermore, we identified >900 primarily intrachromosomal fusions containing canonical splicing sites. Fusions included transcripts from well-known oncogenes, were enriched for proximal genes and in chromosomal regions commonly gained or lost in neuroblastoma. As a proof-of-principle that these fusions can generate altered gene products, we characterized a ZNF451 - BAG2 fusion, producing a truncated BAG2-protein which inhibited retinoic acid induced differentiation. Spliceosome inhibition impeded neuroblastoma fusion expression, induced apoptosis and inhibited xenograft tumor growth. Our findings elucidate a splicing-dependent mechanism generating altered gene products in neuroblastoma and show that the spliceosome is a potential target for clinical intervention.